Characterization of Streptococcus pneumoniae isolates obtained from the middle ear fluid of US children, 2011–2021 - Grant, Lindsay R.; Apodaca, Kevin; Deshpande, Lalitagauri; Kimbrough, John H.; Hayford, Kyla; Yan, Qi; Mendes, Rodrigo; Cané, Alejandro; Gessner, Bradford D.; Arguedas, Adriano (Frontiers in Pediatrics, 2024)
Introduction Pneumococcal conjugate vaccines (PCVs), including higher valency vaccines such as PCV20, have the potential to reduce pediatric otitis media. We assessed serotype distribution, potential PCV coverage, and antimicrobial susceptibility of Streptococcus pneumoniae isolates cultured from middle ear fluid (MEF) of US children age ≤5 years. Methods S. pneumoniae isolates identified from US hospitals participating in the SENTRY Antimicrobial Surveillance program from 2011-2021 were included. Serotypes were determined by in silico analysis based on Pneumococcal Capsular Typing methodology. The percentage of isolates belonging to serotypes included in PCV13 (serotypes 1, 3, 4, 5, 6A, 6B, 7F, 9V, 14, 18C, 19A, 19F, 23F), PCV15 (PCV13 plus 22F, 33F), and PCV20 (PCV13 plus, 8, 10A, 11A, 12F, 15B, 22F and 33F) was calculated. Antimicrobial susceptibility testing was performed by broth microdilution and interpreted using CLSI criteria. Nonsusceptibility was defined as isolates that were intermediate or resistant to a selected antimicrobial. Results Among the 199 S. pneumoniae isolates that were identified, 56.8% were from children age <2 years. Six serotypes accounted for around 60% of isolates: 35B (16.6%), 15B (14.6%), 15A (7.5%), 19A (7.5%), 19F (7.5%), and 3 (7.0%). Serotypes included in PCV13, PCV15, and PCV20 accounted for 23.1%, 30.2%, and 54.8% of isolates, respectively. Overall, 45.2% of isolates were penicillin non-susceptible, and 13.6% were MDR, of which 48% were serotype 19A. Seven serotypes (19A, 15A, 15B, 15C, 23A, 33F, and 35B) accounted for the majority of non-susceptible isolates. Discussion PCVs, particularly PCV20, may prevent a substantial fraction of S. pneumoniae otitis media (OM), including OM due to non-susceptible serotypes. The addition of serotypes 15A, 23A, and 35B would improve coverage against susceptible and non-susceptible pneumococcal OM.